Application of direct oral microscopy in evaluating mucosal margins around invasive oral squamous cell carcinoma - Chomik, Piotr; Michcik, Adam; Michajłowski, Igor; Starzyńska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Direct oral microscopy constitutes a novel, non-invasive diagnostic technique, which aids clinical examination of the oral cavity. The oral mucosa is examined at multiple magnifications and features such as sub-epithelial mucosal vessels, surface patterns, colour tone, transparency and the exact demarcation of mucosal lesions are estimated. The incidence of oral squamous cell carcinoma (OSCC) oscillates between 1.9% and 3.5%, which makes it the eighth most common carcinoma occurring around the world and in Poland. The 5-year survival rates oscillate between 20% and 30%. Aim : The aim of the study was to evaluate clinically unchanged mucosal margins around OSCC by direct oral microscopy. The authors approached the question whether the borders of mucosal margins around OSCC established via direct oral microscopy differ from those established based on clinical examination. Material and methods : Fifteen patients diagnosed with OSCC were enrolled. Patients were first clinically examined to evaluate the extent of the tumour and to plan resection margins. Eventually, direct oral microscopy was performed to establish the width of the subclinically unchanged mucosal margins based on a standard picture of healthy oral mucosae, followed by comparison with those established by clinical evaluation. Results : Histopathologic results of biopsies from areas indicated by direct oral microscopy revealed dysplasia in 86.7% of patients, whereas biopsies from areas indicated by clinical examination revealed dysplasia only in 40% of individuals, resulting in the need for widening of mucosal margins. Conclusions : Direct oral microscopy enables detection of dysplasia within clinically unaltered mucosal margins around OSCC, which results in more precise establishing of resection boundaries, contributing to improvement of resection totality.